Safety and efficacy of a dried aqueous ethanol extract of Melissa officinalis L. leaves when used as a sensory additive for all animal species. (19th February 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of a dried aqueous ethanol extract of Melissa officinalis L. leaves when used as a sensory feed additive for all animal species. The aqueous ethanol extract is specified to contain ≥ 10% of hydroxycinnamic acid derivatives including ≥ 3% of rosmarinic acid. Considering the contradictory data from the Ames tests and uncertainty about the qualitative and quantitative presence of flavonoids and other compounds in the extract from M. officinalis L. leaves, the FEEDAP Panel could not conclude on the genotoxicity of the additive under assessment. Although the identified components of the extract do not raise concerns for the safety of target species, the analysis of the extract is incomplete. In the absence of adequate analytical and safety data, the FEEDAP Panel is unable to conclude on the safety of the additive for the target species. The use of M. officinalis L. leaf dried extract in animal feed at the proposed use level does not raise significantly the exposure levels of the consumer for compounds derived from this plant. However, in the absence of adequate data on genotoxicity, the Panel cannot conclude on the safety for the consumer. In the absence of specific studies, the FEEDAP Panel cannot conclude on the safety of the additive for the user. M. officinalis L. is a native species to Europe and its use in animal nutrition is not expected to pose a risk for the environment. Since M. officinalis L. and its extracts are recognised to flavour food and its function in feed would be essentially the same as that in food, no further demonstration of efficacy is considered necessary for the extract.